POLICY IMPLEMENTATION OF SOCIAL REHABILITATION PROGRAM IN NARCOTICS CORRECTIONAL INSTITUTION CLASS IIA BANDAR LAMPUNG - Silalahi, Yoel Pathur; Pangestuti, Naniek (Universitas Nusa Cendana, 2025)
The purpose of this study was to describe how the implementation of the social rehabilitation program at the Class IIA Narcotics Correctional Institution Bandar Lampung. This research uses descriptive qualitative research methods with data collection techniques in the form of observation, interviews, and documentation studies. The results of this study are that the social rehabilitation program at the Class IIA Bandar Lampung Narcotics Penitentiary is running well, but there are still shortcomings in resource factors such as incomplete facilities and infrastructure and inappropriate officer competence. The limitation of this research is the lack of research time to fully examine social rehabilitation activities. Researchers suggest coordinating with the prison before conducting research so that the research subject is confirmed for further research. Keywords: Social Rehabilitation Program; Correctional Officer; Counselor